Performance and reliability improvement of 905 nm high power laser diode by design, fabrication and characterization of high damage threshold mirrors. (April 2021) - Ghadimi-Mahani, A.; Goodarzi, A.; Farsad, E.; Tahamtan, S.; Nabavi, S.H.
Abstract: The performance improvement of 905 nm InGaAs/AlGaAs/GaAs Single Quantum Well Separate-Confinement Heterostructure Laser Diode (SQW-SCH-LD) in consequence of three-step procedure for facet passivation and protection was demonstrated. Initially, processed InGaAs/AlGaAs/GaAs SQW-SCH LD wafer was scribed and cleaved in ambient atmosphere. Secondly, the air-exposed bar facets were cleaned and impurities were removed with Ar + irradiation and bombardment. Finally, after simulation, mirrors consist of single-layer Al2 O3 as Low-Reflection (LR) and multilayer |(Al2 O3 /Si) 4 | as High-Reflection (HR) coatings were deposited on front and back facets, respectively. Mirror's surface and interface properties were investigated by UV-Vis-NIR Spectroscopy, Atomic Force Microscopy (AFM), Field Emission Scanning Electron Microscopy (FESEM), Burn-in test, Life-time test and Thermography. Spectrophotometer results of coated mirrors were in appropriate adaptation with the simulation results. High magnification FESEM images reveal the precise repeatability stacked Al2 O3 /Si 8-layers with amorphous structure on GaAs substrate. Thermographic image of front facet after life-time reveals that front mirror retains initial quality. In the case of coated front mirror and in Continues-Wave laser mode, laser induce damage threshold (LIDT) improved and increased up to >> 45.75 kW/cm 2 . Improvement in mirror coating process results in enhancement laser reliability and operational parameters such as increasing output power and power efficiency, decreasing degradation rate without any catastrophic optical mirror damage. Highlights: A 3-step procedure was used to improve 905 nm high power laser diode reliability. LR Al2 O3 monolayer and HR (Al2 O3 /Si) 4 multilayer mirrors simulated, coated and tested. 98.2% front mirror transmittance and 97.9% back mirror reflectance obtained at 905 nm. CS-packaged LD show about 3000 h in ACC-mode life time without any COMD event. 250 W CW-laser at ~800 μm beam spot didn't damage front mirror (LIDT>> 45.75 KW/cm 2 ).